Oregano essential oil and its main components Thymol and Carvacrol as alternatives to control citrus canker - Zamuner, Caio Felipe Cavicchia; Marin, Vítor Rodrigues; Dilarri, Guilherme; Hypolito, Giovane Boerner; Sass, Daiane Cristina; Ferreira, Henrique (Frontiers in Agronomy, 2023)
Plant Essential Oils and their constituents are well-known for their properties as antimicrobial agents and are labeled as Generally Recognized as Safe (GRAS), prompting studies around their usage in the control of food-borne microorganisms and phytopathogens. In this study, we evaluated Oregano Essential Oil (OEO), Thymol (THY) and Carvacrol (CAR) for the control of Xanthomonas citri subsp. citri (X. citri). In vitro antibacterial assays revealed that CAR and THY inhibit X. citri growth at the concentrations of 100 µg.mL-1 and 114 µg.mL-1, lower than OEO (136 µg.mL-1). Bactericidal effects were observed at 400 µg.mL-1 for OEO and 200 ug.mL-1 for CAR and THY. Investigating potential cellular targets for the compounds showed that after 30 minutes of exposure up to 84% of the cells had their membranes disrupted, implicating the membrane as the primary target. Phytotoxicity evaluations using Lactuca sativa and Solanum lycopersicum seeds showed an acute toxic effect in all treatments above 200 µg.mL-1, except for OEO and THY in S. lycopersicum at lower concentrations. Regarding their protective effect on citrus leaves, CAR showed no effect when compared to the untreated control (0.39 and 0.50 lesions per cm2, respectively). OEO and THY were able to reduce significantly citrus canker symptoms (0.18 and 0.11 lesions per cm2, respectively). In addition, no toxic effects were observed on citrus leaves in all treatments. THY inhibits X. citri growth and the development of citrus canker lesions. These results show that THY as a viable alternative to be used in citrus canker management.